Food safety control in the poultry industry - Mead, G. C. (Taylor & Francis, 2011)
The book begins by analyzing the main hazards affecting poultry, meat, and eggs, both biological and chemical. It then discusses methods for controlling these hazards at different stages, from the farm through slaughter and carcass processing operations to consumer handling of poultry products. Further chapters review established and emerging techniques for decontaminating eggs or processed carcasses, from physical methods to the use of bacteriophage and bacteriocins.